Les effets de la technologie et la protection des droits des consommateurs dans le paiement bancaire - L’Heureux, Nicole (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1983)
The development of computer and communication technology applied to payment by cheques has eliminated several manual operations, reduced the number of documents transfered and accelerated the time processing of payments. With these changes, there is more than a technical novelty and a simple mechanization of banking business. The general practices of banking and the relationship between financial institutions and their clients are affected. In the new system the rights of consumers are of great concern. The author illustrates some problems arising and the necessity of the intervention of the legislator to provide a basic framework establishing rights, liabilities and responsibility of all parties involved and to insure greater protection for the individual consumer's rights.